Potential deoxycytidine kinase inhibitory activity of amaryllidaceae alkaloids: An in silico approach - Bashir A Yousef; Amina I Dirar; Mohamed Ahmed A Elbadawi; Mohamed K Awadalla; Magdi A Mohamed (Wolters Kluwer Medknow Publications, 2018)
Background: Plants of the Amaryllidaceae family have been under intense scrutiny for the presence of a couple of alkaloidal secondary metabolites with endued cytotoxic activity, such as pancratistatin (1), 7-deoxypancratistatin (2), narciclasine (3), 7-deoxynarciclasine (4), trans-dihydronarciclasine (5), and 7-deoxy-trans-dihydronarciclasine (6). Nevertheless, preclinical evaluation of these alkaloids has been put on hold because of the limited quantity of materials available from isolation. Aim: To explore the underlying cytotoxic molecular mechanisms of the Amaryllidaceae alkaloids (1-6) and to assess their absorption, distribution, metabolism, excretion, and toxicity (ADMET) profiles using chemoinformatic tools. Materials And Methods: AutoDock 4.0 software along with different in silico chemoinformatic tools, namely PharmMapper, Molinspiration, MetaPrint2D, and admetSAR servers, were used to assess the drugability of the Amaryllidaceae alkaloids (1-6). Results: Deoxycytidine kinase (dCK) (PDB: 1P60) was predicted as a potential target with fitting score of 5.574. In silico molecular docking of (1-6) into dCK revealed good interactions, where interesting hydrogen bonds were observed with the amino acid residues-Gly-28 and Ser-35-located in the highly conserved P-loop motif. This motif plays a special role in dCK function. Contrary to (1), in silico pharmacokinetic results have shown good absorption and permeation and thus good oral bioavailability for (2-6). Conclusion: The in silico docking data have proposed that the reported cytotoxic activity of the Amaryllidaceae alkaloids (1-6) could be mediated through dCK inhibition. In addition, the ADMET profile of these alkaloids is promising and thus (1-6) could be candidates for future drug development.